2018
DOI: 10.3389/fmicb.2018.01439
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus acidophilus Attenuates Salmonella-Induced Stress of Epithelial Cells by Modulating Tight-Junction Genes and Cytokine Responses

Abstract: Scope: Salmonellosis is a prevalent food-borne illness that causes diarrhea in over 130 million humans yearly and can lead to death. There is an urgent need to find alternatives to antibiotics as many salmonellae are now multidrug resistant. As such, specific beneficial bacteria and dietary fibers can be an alternative as they may prevent Salmonella Typhimurium (STM) infection and spreading by strengthening intestinal barrier function.Methods and Results: We tested whether immune active long-chain inulin-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 53 publications
3
30
0
Order By: Relevance
“…However, the mood elevation could be due to recovery of gastrointestinal symptoms rather than effect of probiotics solely. Both in vitro and in vivo models showed that L. acidophilus protects the intestinal barrier integrity by preventing pathogen adherence and release of proinflammatory cytokines (Chen et al, 2009;Justino et al, 2015;Alamdary et al, 2018;Lepine et al, 2018;Najarian et al, 2019). Taken together, B. bifidum and L. acidophilus potentially exhibit antidepressive effect and their direct influence on depression warrants further investigation.…”
Section: Candidate Probiotics With Potential Antidepressive Effectmentioning
confidence: 95%
“…However, the mood elevation could be due to recovery of gastrointestinal symptoms rather than effect of probiotics solely. Both in vitro and in vivo models showed that L. acidophilus protects the intestinal barrier integrity by preventing pathogen adherence and release of proinflammatory cytokines (Chen et al, 2009;Justino et al, 2015;Alamdary et al, 2018;Lepine et al, 2018;Najarian et al, 2019). Taken together, B. bifidum and L. acidophilus potentially exhibit antidepressive effect and their direct influence on depression warrants further investigation.…”
Section: Candidate Probiotics With Potential Antidepressive Effectmentioning
confidence: 95%
“…As a crucial component of the epithelial barrier, they are often targeted by pathogenic bacteria, aiding infection and the development of disease [14]. L. acidophilus attenuated Salmonella -induced stress of epithelial cells by modulating TJs genes [15]. B. subtilis significantly enhanced intestinal barrier integrity by up-regulating tight junction protein expression [16].…”
Section: Introductionmentioning
confidence: 99%
“…A similar response was observed by Wagar et al (2009) in which a milk blend fermented by S. thermophilus ST5 and Bifidobacterium longum R0175 significantly reduced the levels of IL-8 produced compared with an acidified milk blend treatment. After stimulation by Salmonella Typhimurium, L. acidophilus W37-treated epithelial cells also displayed decreased amounts of IL-8 (Lépine et al, 2018). Additionally, the immunomodulatory effect of Lactococcus lactis NCDO 2118 demonstrated reduced secretion of IL-8 in vitro (Luerce et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…Interleukin-8 is a proinflammatory cytokine produced by a variety of cell types, including intestinal epithelial cells (Eckmann et al, 1993;Imaoka et al, 2008). There is considerable evidence reporting that LAB and their fermented milks display an overall modulating effect in in vitro studies, specifically in the presence of pathogens, which stimulate inflammatory responses (Zeinhom et al, 2012;Zagato et al, 2014;Chen et al, 2016;Acurcio et al, 2017;Lépine et al, 2018). Although similar to this study, others have reported considerably less production of IL-8 by Caco-2 cells compared with other cell types, including HT-29 and its subsets (Eckmann et al, 1993;Zhang et al, 2005;Ren et al, 2013).…”
Section: Discussionmentioning
confidence: 99%